Implementation and control of a cascaded boost converter - Chong Kwee Ching (2017)
In this report, the design, implementation and control of a cascaded boost converter are presented. Three types of controller are implemented. The three controllers for the regulation of the converter are the non-adaptive controller, adaptive controller and adaptive controller with current integrator. The controller under different operating conditions are presented and evaluated. Experiment results showing the features of the controller will be presented.